A Novel Method of Extending Glaucoma Drainage Tube: "Tube-in-Tube" Technique. Issue 2 (February 2017) - Chiang, Mark Yu-Ming; Camuglia, Jayne E.; Khaw, Peng Tee
Abstract : Purpose: To describe a new and simple technique of glaucoma tube extension that carries several advantages over previously described techniques. Patients and Methods: A retrospective noncomparative case series of 3 patients (1 adult and 2 pediatric cases) with glaucoma tube retraction managed by the "tube-in-tube" technique. The follow-up duration ranges from 1 month to 3 years. Results: Adequate tube position and length were seen in all cases throughout the follow-up period. No tube migration was seen. The intraocular pressures were significantly reduced and maintained in all cases. There was no visual loss as a result of the procedure. Conclusions: This new "tube-in-tube" glaucoma drainage device tube extension technique is safe and simple to perform, and has many advantages over previously reported techniques. It can be used in both the adult and pediatric glaucoma population, and is not limited to the type of drainage implants.